2019
DOI: 10.1080/13543784.2019.1654994
|View full text |Cite
|
Sign up to set email alerts
|

Agents in early development for treatment of bladder dysfunction – promise of drugs acting at TRP channels?

Abstract: Introduction: In the lower urinary tract (LUT) several members of the TRP superfamily are involved in nociception and mechanosensory transduction. Animal studies have suggested a therapeutic potential of some of these channels, including TRPV1, TRPV4, TRPM8, TRPA1, and TRPM4, for treatment of bladder over-and underactivity and bladder pain disorders, but translation of this information to clinical application has been slow. Areas covered: An update on and discussion of current information on the potential clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 67 publications
0
13
0
2
Order By: Relevance
“…[ 272,273 ] A number of treatments, ranging from medications to surgical interventions, have been developed with the hope of treating this condition. [ 274–278 ] However, due to the fact that neurogenic bladder dysfunction can arise from a number of conditions, including Parkinson's Disease, stroke, brain injury, and multiple sclerosis, developing a universal treatment for this condition remains a challenge. [ 279 ] Neurogenic bladder dysfunction has differing results which can range from an overactive bladder, to difficulty passing urine.…”
Section: Neural Engineeringmentioning
confidence: 99%
“…[ 272,273 ] A number of treatments, ranging from medications to surgical interventions, have been developed with the hope of treating this condition. [ 274–278 ] However, due to the fact that neurogenic bladder dysfunction can arise from a number of conditions, including Parkinson's Disease, stroke, brain injury, and multiple sclerosis, developing a universal treatment for this condition remains a challenge. [ 279 ] Neurogenic bladder dysfunction has differing results which can range from an overactive bladder, to difficulty passing urine.…”
Section: Neural Engineeringmentioning
confidence: 99%
“…In contrast, phosphodiesterase type 5 inhibitors, and the substance P and calcitonin gene‐related peptide release inhibitor, cizolirtine, were found to be effective and safe in phase II clinical studies, but not pursued further; a specific response subset of patients has not been identified for any of them. Thus, reawakening an interest of major pharmaceutical companies in OAB might only occur when academic research identifies not only potential therapeutic targets, but also biomarkers to identify patient populations in which responsiveness to addressing these targets is markedly enriched, and translational animals models for such pathophysiology‐defined subsets (Table ) . An example of this could be nerve growth factor, but the evidence for this or other urinary markers at present is insufficiently robust to identify patient populations in which novel treatments might have greater efficacy than existing treatments …”
Section: Future Research Needsmentioning
confidence: 99%
“…Thus, reawakening an interest of major pharmaceutical companies in OAB might only occur when academic research identifies not only potential therapeutic targets, but also biomarkers to identify patient populations in which responsiveness to addressing these targets is markedly enriched, and translational animals models for such pathophysiology-defined subsets ( Table 3). [39][40][41] An example of this could be nerve growth factor, 53 but the evidence for this or other urinary markers at present is insufficiently robust to identify patient populations in which novel treatments might have greater efficacy than existing treatments. 54…”
Section: Future Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Особливу увагу приділяють каналам транзієнтного рецепторного потенціалу (TRP), що експресуються в епітеліальних, нервових і гладеньком'язових клітинах (ГМК). У багатьох наукових роботах показано їх участь у регуляції судинного тонусу, моторики кишечника, скоротливості сечового міхура та матки, проте механізми активації цих каналів вивчені недостатньо [3]. Відсутність такої ключової інформації відкриває перспективу подальшої роботи в цьому напрямі, спрямовуючи її у фокус актуальних клінічних проблем.…”
unclassified